ANALISIS KING’S SCORE DI PENYAKIT HATI KRONIS BERDASARKAN FIBROSCAN - Wira Wira; Amaliyah T. Lopa; Ibrahim Abdul Samad (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
Chronic liver disease is a commonly found disease in Indonesia and remains a serious health problem. Chronic liver disease oftenprogresses to hepatic cirrhosis or hepatoma initiated by fibrotic process in liver. Liver biopsy result is a gold standard in determining theliver fibrosis degree, but it has some limitations. King’s Score is a non-invasive method that uses routine laboratory predictors relatedto liver fibrosis. Therefore, it is necessary to know the diagnostic value of King’s Score in determining the fibrosis degree of liver chronicdisease by using fibro scan as the gold standard in stead of biopsy. This study was a retrospective study with data collected from themedical records from the Medical Record Installation at the Dr. Wahidin Sudirohusodo General Hospital between January 2011 up toDecember 2013. The study results derived from 99 samples with Spearman correlation test showed a significant relationship between theKing’s Score and fibrosis degree of chronic liver disease (p=0.000 and r=0.651). The analysis of the receiver operating characteristics(ROC) indicated that in mild and moderate fibrosis the AUC value was too weak, whereas in heavy fibrosis the AUC value was 0.860,which was statistically very strong with a cut-off value of 7.15 and with a 80.6% sensitivity, and a 75.0% specificity, Positive PredictiveValue59.5%, Negative Predictive Value 89.5%. This meant that the King’s Score value of >7.15 could be used as a heavy fibrosis degreepredictor in chronic liver patients. Further studies are needed to analyze the King’s Score based on chronic liver disease etiology and usea liver biopsy as the gold standard in determining the degree of liver fibrosis.